Simultaneous resection for colorectal cancer with synchronous liver metastases is a safe procedure: Outcomes at a single center in Turkey - ERDİM, AYLİN; DULUNDU, ENDER; GÜNAL, ÖMER; YEGEN, ŞEVKET CUMHUR (IRCA-BSSA, 2017)
The optimal surgical strategy for treating colorectal cancer with synchronous liver metastases is subject to debate. The current study sought to evaluate the outcomes of simultaneous colorectal cancer and liver metastases resection in a single center. Prospectively collected data on all patients with synchronous colorectal liver metastases who underwent simultaneous resection with curative intent were analyzed retrospectively. Patient outcomes were compared depending on the primary tumor location and type of liver resection (major or minor). Between January 2005 and August 2016, 108 patients underwent simultaneous resection of primary colorectal cancer and liver metastases. The tumor was localized to the right side of the colon in 24 patients (22%), to the left side in 40 (37%), and to the rectum in 44 (41%). Perioperative mortality occurred in 3 patients (3%). Postoperative complications were noted in 32 patients (30%), and most of these complications (75%) were grade 1 to 3 according to the Clavien-Dindo classification. Neither perioperative mortality nor the rate of postoperative complications after simultaneous resection differed among patients with cancer of the right side of the colon, those with cancer of the left side of the colon, and those with rectal cancer (4%, 2.5%, and 2%, respectively, p = 0.89) and (17%, 33%, and 34%, respectively; p = 0.29)]. The 5-year overall survival of the entire sample was 54% and the 3-year overall survival was 67 %. In conclusion, simultaneous resection for primary colorectal cancer and liver metastases is a safe procedure and can be performed without excess morbidity in carefully selected patients regardless of the location of the primary tumor and type of hepatectomy.
Keywords: Liver metastases; colorectal cancer; synchronous; simultaneous resection; SURGICAL MARGIN STATUS; LONG-TERM SURVIVAL; HEPATIC RESECTION; POSTOPERATIVE COMPLICATIONS; IMPACT; RECURRENCE; MANAGEMENT; MORBIDITY; SURGERY; CHEMOTHERAPY